Fertlizaton of onion with phosphorus and potassium in an area with residual fertlizaton of tomato - Wamser, Anderson Fernando (2020)
The aim of this study was to evaluate the response of onion crops to phosphorus and potassium fertlizaton in areas of succession to the tomato. Two experiments were conducted in the 2009 season, in an area of no-tll vegetable area and another in conventonal plantng of vegetables. The experimental design was a randomized complete block with fve replicatons and four treatments (zero, 50%, 100% and 150% of the recommended doses of P and K for onion crops). The recommended doses were 120kg/ ha of P2O5 and 90kg/ha of K2O. The variables were marketable yield and average bulb weight. The marketable yield of onion wasnot aﬀected by the levels of P and K, except for bulb yield class 4, which showed higher values as of 50% of the recommended dose.